Heavy metal-free sulfur-containing free-cutting titanium alloy and preparation method thereof

Through sulfur-containing easy-to-cut titanium alloy materials without adding heavy metals and unique preparation technology, the problems of high temperature, high hardness and serious work hardening of titanium alloys during cutting are solved, which significantly improves cutting performance and thermal processing performance and reduces costs.

CN119843106AActive Publication Date: 2025-04-18CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD

Patent Information

Application Number
CN202510350693.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

During the cutting process, the cutting zone temperature, hardness and severe work hardening, high chemical activity and low elastic modulus, resulting in severe tool wear and poor processing accuracy and surface quality. In addition, heavy metals are added to improve cutting performance in traditional methods, and there are cost and biocompatibility problems.

Method used

A sulfur-containing easy-to-cut titanium alloy material without adding heavy metals is used, with components such as S: 0.2-0.4%, O: 0.3-0.45%, B: 0.003-0.006%, C≤0.03%, N≤0.03%. Titanium sponge was produced by the Kroll method and was crushed and baked in multiple stages, followed by thermal isostatic sintering to form a uniformly distributed titanium sulfur compound, avoiding Ti and S separation and heavy metal addition during liquid smelting.

Benefits of technology

It significantly improves the cutting performance of titanium alloy, solves the uniformity of elements S and B distribution, avoids cracking of hot-processed surfaces, shortens production cycles, reduces costs, and improves the thermal processing performance and biocompatibility of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843106A_ABST
    Figure CN119843106A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-containing free-cutting titanium alloy without heavy metal and a preparation method thereof, and belongs to the field of nonferrous metal materials. The free-cutting titanium alloy material comprises the following components in percentage by mass: S: 0.2-0.4%; 0.3 to 0.45 percent of O; b: 0.003% to 0.006%; c is less than or equal to 0.03%; less than or equal to 0.03% of N, and the balance titanium and unavoidable impurities. The invention further discloses a preparation method of the raw material sponge titanium of the free-cutting titanium alloy material and a method for preparing the free-cutting titanium alloy material. Through unique component design and a preparation process, addition of heavy metal for fixing S in the free-cutting titanium alloy is avoided, so that the titanium alloy is better in biocompatibility, titanium-sulfur compounds in the titanium alloy are uniformly distributed, the chip breaking property and the tool nose lubricating condition are improved, and the service life of the free-cutting titanium alloy is prolonged. The problems of distribution uniformity of the element S and the element B and cracking of the hot working surface of the titanium alloy material containing the element S are solved, the production period is shortened, the cost is reduced, and the cutting performance of the titanium alloy is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nonferrous metal materials, and in particular to a sulfur-containing free-cutting titanium alloy without adding heavy metals and a preparation method thereof. Background Art

[0002] Titanium and titanium alloys have been widely used in aerospace, automobile manufacturing, medical equipment and many other fields due to their low density, high strength, good corrosion resistance, excellent biocompatibility and many other advantages. However, the poor cutting performance of titanium alloys (also known as titanium materials) has severely limited its efficient processing and wide application in industrial production, as shown below: High temperature in the cutting zone: Titanium has a low thermal conductivity, which is only one-fourth of that of iron. During the cutting process, the heat generated is difficult to discharge and accumulates on the cutting edge, causing the temperature in the cutting zone to rise sharply, which not only accelerates the wear of the tool, but also affects the surface quality and dimensional accuracy of the machined parts.

[0003] High hardness and severe work hardening: Titanium will experience significant work hardening during processing, and its surface is prone to react with gases in the air to form a "tissue hardening layer". This greatly increases the cutting force on the tool during cutting, aggravates tool wear, and even causes tool breakage, which seriously reduces the tool life and increases processing costs.

[0004] High chemical activity: Titanium has high chemical activity and will react chemically with the components in the tool during the cutting process, resulting in an increase in the friction coefficient between the tool and the titanium material and a serious phenomenon of tool sticking. A large amount of heat is concentrated on the blade, further aggravating the wear of the tool and affecting the processing accuracy and surface quality.

[0005] Low elastic modulus: Titanium has a low elastic modulus and is prone to springback during processing. This will not only cause stress on the back of the tool, aggravating tool wear, but also seriously affect the surface accuracy of the processed parts, resulting in large processing size deviations, making it difficult to meet high-precision processing requirements.

[0006] At present, in order to improve the cutting performance of titanium materials, research is mainly carried out in the following three directions: Develop high-performance cutting tools: Research and develop high-hardness, high-toughness, and high-temperature resistant cutting tool materials, such as carbide tools and ceramic tools, to improve the wear resistance and heat resistance of the tools and adapt to the cutting of titanium materials. However, these high-performance tools are expensive and still cannot fully meet the needs of efficient and high-precision processing of titanium materials under certain complex processing conditions.

[0007] Improve cutting conditions: Use ultra-low temperature processing or suitable cooling and lubricating media to reduce the temperature of the cutting zone, reduce tool wear and work hardening. Ultra-low temperature processing requires special equipment and processes, and is costly; and although choosing a suitable cooling and lubricating medium can improve the processing conditions to a certain extent, the effect on improving cutting performance is limited, and it may cause environmental pollution and other problems.

[0008] Design easy-to-cut material components and microstructures: On the one hand, by optimizing the strength-plasticity matching of titanium metal, reducing the strength-plasticity product, thereby reducing cutting resistance; on the other hand, adding precipitate-forming elements to promote the formation of a second phase that is brittle, has weak interface bonding, or has a certain lubricating effect, thereby improving the chip breaking property of titanium metal. However, there are many problems in the implementation of traditional methods, such as the addition of certain elements may lead to increased costs and poor biocompatibility.

[0009] In addition, S is a free-cutting element. Adding S to titanium is beneficial to improving cutting performance. The principle is that S combines with Ti to form a free-cutting sulfur-titanium compound. However, when using the traditional smelting method, liquid S and Ti will be stratified after the sponge titanium is melted, resulting in the inability to evenly distribute the sulfur-titanium compound, affecting the improvement of cutting performance. Therefore, heavy metal elements such as rare earth that can fix S must be added to the existing free-cutting titanium alloy composition. Moreover, as the S content in titanium increases, the hot working performance of titanium will be greatly reduced, especially the surface is prone to cracking, which seriously restricts the development and application of free-cutting titanium alloys containing S.

[0010] In summary, the existing methods for improving the cutting performance of titanium materials have various limitations. It is of great practical significance to develop a sulfur-containing free-cutting titanium alloy and its preparation method that does not add heavy metals, has low cost, excellent cutting performance and stable hot working performance. Summary of the invention

[0011] Based on this, and in view of the deficiencies of the above-mentioned prior art, a sulfur-containing free-cutting titanium alloy without adding heavy metals and a preparation method thereof are provided, aiming to solve the problems of high cost and poor biocompatibility of existing free-cutting titanium alloys, as well as uneven element distribution and hot working surface cracking during the processing of S-containing titanium alloys, and further apply the free-cutting titanium alloy to the fields of human body contact equipment and food processing equipment.

[0012] In order to achieve the above purpose, the following technical solutions are adopted: The invention provides a sulfur-containing free-cutting titanium alloy material without adding heavy metals. The components of the sulfur-containing free-cutting titanium alloy material are as follows by mass percentage: S: 0.2-0.4%; O: 0.3-0.45%; B: 0.003-0.006%; C≤0.03%; N≤0.03%, and the balance is titanium and unavoidable impurities.

[0013] In some embodiments, the composition of the sulfur-containing free-cutting titanium alloy material is calculated by mass percentage as follows: S: 0.4%; O: 0.3%; B: 0.003%; C≤0.03%; N≤0.03%, and the remainder is titanium and unavoidable impurities.

[0014] In some embodiments, the composition of the sulfur-containing free-cutting titanium alloy material is calculated by mass percentage as follows: S: 0.2%; O: 0.4%; B: 0.006%; C≤0.03%; N≤0.03%, and the remainder is titanium and unavoidable impurities.

[0015] The present invention also provides a method for preparing raw material sponge titanium according to the sulfur-containing free-cutting titanium alloy material as described above, comprising the following steps: S101. In the Kroll process, TiCl4 gas, H2S gas and BCl3 gas are simultaneously introduced into the reactor; S102. Titanium sponge particles having a maximum particle diameter of ≤6 mm are obtained by distillation and multi-stage crushing; S103. Spread the titanium sponge particles flat and place them in an oven at 500-550° C. for 50-90 minutes.

[0016] In some embodiments, the multi-stage crushing includes three stages of crushing steps, namely jaw crushing, cone crushing and roller crushing, performed sequentially.

[0017] In some embodiments, in step S101, the molar ratio of Ti:S is controlled to be 99:(0.36-0.71), and the molar ratio of Ti:B is controlled to be 99:(0.006-0.012).

[0018] The present invention also provides a method for preparing the free-cutting titanium alloy material as described above from the titanium sponge particles obtained by the preparation method as described above, comprising: The titanium sponge particles are pressed into blanks; the blanks are stacked and placed in a TA1 package and vacuum-sealed; hot isostatic pressing and sintering are performed under argon protection to obtain square billets for rolling; the sintered square billets are heated to 900-930° C. and then rolled into free-cutting titanium alloy material discs through a hot rolling unit.

[0019] In some embodiments, the step of “pressing titanium sponge particles into a blank” comprises: The titanium sponge particles are pressed into blanks at a pressure of 500 to 900 MPa.

[0020] In some embodiments, during the hot isostatic pressing step: The sintering temperature is 900-1000°C, the pressure is 90-100MPa, and the sintering time is 3-5h.

[0021] In some embodiments, the heating rate of the hot isostatic pressing sintering is 2-5° C. / min.

[0022] The present invention has the following beneficial technical effects: The present invention avoids the separation of Ti and S in the liquid smelting process through unique component design and preparation process, and avoids the addition of heavy metals necessary for fixing S through solid-state sintering. At the same time, the titanium sulfur compound in the titanium alloy is evenly distributed, the chip breaking property and the tool tip lubrication condition are improved, and the problem of uniform distribution of element S and element B is solved. By adopting an external S-free sheath, the good processability of the outer sheath is utilized to avoid the S-containing part that is difficult to process being exposed to the outside, and the problem of hot processing surface cracking of titanium alloy materials containing element S is solved, the production cycle is shortened, the cost is reduced, and the cutting performance of titanium alloy is significantly improved.

[0023] The sulfur-containing free-cutting titanium alloy material without adding heavy metals of the present invention comprises a titanium sulfur compound with a layered structure, the titanium sulfur compound is soft and easy to slip between layers, and the uniformly distributed titanium sulfur compound has the effect of improving the chip breaking property of the cutting and improving the lubrication condition of the tool tip. The titanium alloy contains boron, which is a grain refining element in the titanium alloy, and fine grains are more conducive to high-temperature deformation, reducing high-temperature rheological stress and preventing deformation cracking. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 A flow chart of the method for preparing a free-cutting titanium alloy material according to the present invention; Figure 2 The metallographic diagram of the free-cutting titanium alloy material of Example 1 of the present invention; Figure 3 This is a metallographic diagram of the free-cutting titanium alloy material of Example 2 of the present invention; Figure 4 This is the metallographic diagram of the titanium alloy material of the comparative example. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0027] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.

[0028] Based on the above-mentioned purpose, the first aspect of an embodiment of the present invention provides a sulfur-containing free-cutting titanium alloy material without adding heavy metals, and the composition of the sulfur-containing free-cutting titanium alloy material is calculated by mass percentage as follows: S: 0.2~0.4%; O: 0.3~0.45%; B: 0.003~0.006%; C≤0.03%; N≤0.03%, and the remainder is other unavoidable impurities in titanium and sponge titanium, mainly including Fe, Si, Mg, H, etc., and the content of a single impurity in the unavoidable impurities is required to be ≤0.05%, and the sum of the contents of the unavoidable impurities is ≤0.1%.

[0029] According to a second aspect of the embodiments of the present invention, a method for preparing a sulfur-containing free-cutting titanium alloy material is provided. Figure 1 Shown is a schematic flow chart of the method.

[0030] like Figure 1 As shown in , the preparation may include the following steps: S101. In the Kroll process, TiCl4 gas, H2S gas and BCl3 gas are simultaneously introduced into the reactor; S102. Titanium sponge particles having a maximum particle diameter of ≤6 mm are obtained by distillation and multi-stage crushing; S103. Spread the titanium sponge particles flat and place them in an oven at 500-550° C. for 50-90 minutes.

[0031] S104. Pressing titanium sponge particles into billets; stacking the billets into a TA1 package and sealing the package by vacuuming; hot isostatic pressing and sintering under argon protection to obtain a square billet for rolling; heating the sintered square billet to 900-930° C. and rolling it into a free-cutting titanium alloy material disc through a hot rolling unit.

[0032] Among them, S101-S103 are methods for preparing sponge titanium, a raw material for sulfur-containing free-cutting titanium alloy materials, in which the oxygen content is increased, so that the main effective element content of the sponge titanium obtained is S: 0.2~0.4%; O: 0.3~0.45%; B: 0.003~0.006%; S104 is a method for preparing sponge titanium particles prepared by S101-S103 into free-cutting titanium alloy materials.

[0033] In a preferred embodiment of the present invention, the multi-stage crushing includes three stages of crushing steps of jaw crushing, cone crushing and roller crushing performed sequentially.

[0034] In a preferred embodiment of the present invention, in step S101, the molar ratio of Ti:S is controlled to be 99:(0.36-0.71), and the molar ratio of Ti:B is controlled to be 99:(0.006-0.012).

[0035] In a preferred embodiment of the present invention, the step of "pressing titanium sponge particles into a blank" comprises: The titanium sponge particles are pressed into blanks at a pressure of 500 to 900 MPa.

[0036] In a preferred embodiment of the present invention, in the hot isostatic pressing sintering step: the sintering temperature is 900-1000° C., the pressure is 90-100 MPa, and the sintering time is 3-5 hours.

[0037] In a preferred embodiment of the present invention, the heating rate of hot isostatic pressing sintering is 2-5° C. / min.

[0038] In a preferred embodiment of the present invention, the hot rolling mill group includes a roughing mill group, a medium rolling mill group and a finishing mill group arranged in sequence, and the total deformation elongation is ≥120.

[0039] In a preferred embodiment of the present invention, the wall thickness of the TA1 package is 10-15 mm, and the residual pressure after vacuuming is .

[0040] In a preferred embodiment of the present invention, the bulk density of the titanium sponge particles is 2.2 to 2.5 g / cm³.

[0041] The preparation method of the present invention does not involve a liquid smelting process, and alloy elements are introduced into the titanium sponge during the preparation stage, thereby solving the problem of uniform distribution of the main easy-cutting element S and the grain growth inhibiting element B, and overcoming the stratification problem of liquid S and Ti in the traditional smelting method.

[0042] The method of block heating and isostatic pressing is adopted to coat the surface of the square billet with a layer of TA1 with excellent deformation performance, which solves the problem of surface cracking of S-containing titanium materials during hot processing.

[0043] The traditional multiple smelting and forging process is shortened to one hot isostatic pressing process, which shortens the production and processing cycle. At the same time, hot isostatic pressing can form the blank completely without the need for ingot peeling or blank surface milling and grinding, which improves the raw material utilization rate and reduces production costs.

[0044] Improved cutting performance: The titanium alloy of the present invention contains a layered titanium-sulfur compound, which is soft and prone to interlayer slippage. During the cutting process, the uniformly distributed titanium-sulfur compound can improve the chip breaking property of the chips, making the chips easier to break and discharge, and can also improve the lubrication conditions of the tool tip, reduce the friction between the tool and the titanium alloy, and reduce the cutting force, thereby significantly improving the cutting performance of the titanium alloy.

[0045] Grain refinement and improved processing performance: Boron contained in the alloy is a grain refinement element. During the solidification and processing of titanium alloy, boron can inhibit the growth of grains and form a fine grain structure of titanium alloy. Fine grains are more conducive to high-temperature deformation, reduce high-temperature rheological stress, improve the plasticity and toughness of the material, effectively prevent deformation and cracking during processing, and improve the hot processing performance of titanium alloy.

[0046] Improved uniformity of element distribution: The present invention does not have the traditional liquid smelting process, but instead places the alloy elements S and B in the preparation stage of sponge titanium. By adding H2S and BCl3 gases during the reduction process of producing sponge titanium by the Kroll method, S and B are evenly distributed in the sponge titanium, solving the problem of uniform distribution of the main free-cutting element S and the grain growth inhibiting element B, and overcoming the difficulty of stratification of liquid S and Ti in the traditional smelting method.

[0047] Solution to the hot working surface cracking problem: The billet surface is coated with a layer of TA1 with excellent deformation performance by using the block heating isostatic pressing method. TA1 can effectively protect the surface of S-containing titanium materials during hot working, alleviate the hot working surface cracking problem caused by the increase of S content, and ensure the quality and performance stability of titanium alloy during hot working.

[0048] Reduced production costs: The traditional multiple melting and forging process is shortened to one hot isostatic pressing process, which simplifies the production process and shortens the production cycle. At the same time, the hot isostatic pressing net near-forming technology does not require ingot peeling, billet surface milling and grinding, etc., which reduces material loss and improves raw material utilization, thereby reducing production costs and improving product market competitiveness.

[0049] The present invention is further illustrated by the following examples.

[0050] Example 1 A sulfur-containing free-cutting titanium alloy without adding heavy metals, the mass percentage of which is: S: 0.4%; O: 0.3%; B: 0.003%; C≤0.03%; N≤0.03%, the balance is titanium and unavoidable impurities, the content of a single impurity among the unavoidable impurities is required to be ≤0.05%, and the sum of the unavoidable impurities is required to be ≤0.1%.

[0051] The preparation method of the above sulfur-containing free-cutting titanium alloy without adding heavy metals is as follows: The Kroll method is used to produce titanium sponge. During the reduction process, TiCl4 gas, H2S gas and BCl3 gas are mixed and added, and the ratio of each gas is determined according to Ti:S=99:0.71, Ti:B=99:0.006.

[0052] The titanium sponge lump obtained in the above steps is crushed by a multi-stage crusher, and the crushed material is sieved by a vibrating screen with a mesh diameter of 6 mm. The large particles are sent back to the crusher, and the small particles enter the next step.

[0053] The titanium sponge obtained in the above steps is spread on a tray with a thickness of ≤40 cm, and is placed in an oven at 500° C. for baking for 60 minutes.

[0054] The titanium sponge obtained in the above steps was placed in a square mold and pressed into a 175 mm cubic sintered block using an 8000 ton hydraulic press at a pressing pressure of 600 MPa.

[0055] 30 pieces of titanium sponge sintered blocks obtained in the above steps were placed into a rectangular box formed by welding 2mm TA1 titanium plates, the inner cavity size of the box was 175mm×175mm×5250mm, and welded and sealed in a vacuum welding box to obtain a sintered blank.

[0056] The sintered billet was placed in an argon protected hot isostatic pressing furnace for sintering at a sintering temperature of 900°C, a pressure of 90 MPa, and a sintering time of 4 h to obtain a square billet for rolling.

[0057] The square billet is heated to 900-930°C and rolled by a hot rolling mill to obtain a sulfur-containing free-cutting titanium alloy disc without adding heavy metals.

[0058] Example 2 A sulfur-containing free-cutting titanium alloy without adding heavy metals, the mass percentage of which is: S: 0.2%; O: 0.4%; B: 0.006%; C≤0.03%; N≤0.03%, the balance is titanium and unavoidable impurities, the content of a single impurity among the unavoidable impurities is required to be ≤0.05%, and the sum of the unavoidable impurities is required to be ≤0.1%.

[0059] The preparation method of the above sulfur-containing free-cutting titanium alloy without adding heavy metals is as follows: The Kroll method is used to produce titanium sponge. During the reduction process, TiCl4, H2S and BCl3 are mixed and added, and the ratio of each gas is determined according to Ti:S=99:0.36 and Ti:B=99:0.012.

[0060] The titanium sponge lump obtained in the above steps is crushed by a multi-stage crusher, and the crushed material is sieved by a vibrating screen with a mesh diameter of 6 mm. The large particles are sent back to the crusher, and the small particles enter the next step.

[0061] The titanium sponge obtained in the above steps was spread on a tray with a thickness of ≤40 cm, and placed in an oven at 550° C. for baking for 90 minutes.

[0062] The titanium sponge obtained in the above steps was placed in a square mold and pressed into a 175 mm cubic sintered block using an 8000 ton hydraulic press at a pressing pressure of 600 MPa.

[0063] 30 pieces of titanium sponge sintered blocks obtained in the above steps were placed into a rectangular box formed by welding 2mm TA1 titanium plates, the inner cavity size of the box was 175mm×175mm×5250mm, and welded and sealed in a vacuum welding box to obtain a sintered blank.

[0064] The sintered billet was placed in an argon protected hot isostatic pressing furnace for sintering at a sintering temperature of 900°C, a pressure of 90 MPa, and a sintering time of 4 h to obtain a square billet for rolling.

[0065] The square billet is heated to 900-930°C and rolled by a hot rolling mill to obtain a sulfur-containing free-cutting titanium alloy disc without adding heavy metals.

[0066] Comparative Example A titanium alloy, whose components by mass percentage are: O: 0.3%; B: 0.006%; C≤0.03%; N≤0.03%, and the balance is titanium and unavoidable impurities, wherein the content of a single impurity among the unavoidable impurities is required to be ≤0.05%, and the sum of the contents of the unavoidable impurities is required to be ≤0.1%.

[0067] The preparation method of the titanium alloy is as follows: The titanium alloy was melted in a vacuum consumable electrode shell furnace at a temperature of 1680°C for 20 minutes, and the titanium alloy melt was filled with the membrane shell by negative pressure casting. The vacuum degree of negative pressure casting was 50pa, and the negative pressure was 0.1Mpa. The titanium alloy faucet blank undergoes solution and aging antibacterial heat treatment. The solution heat treatment is to put the furnace into the room temperature, heat up with the furnace, the heating rate is 10℃ / minute, the solution temperature is 830℃, the solution time is 5h, and it is water cooled to room temperature; the aging temperature is 450℃, and the aging time is 16h.

[0068] The following methods were used to test the performance of the embodiments and comparative examples of the present invention: (1) Hardness test: The hardness test of the embodiment and the comparative example was carried out using a micro Vickers hardness tester. The test standard was GBT 4340.1-2009 Metallic Material Vickers Hardness Test. The load was 500 g. Each sample was tested 4 times, and the average value was selected as the final result.

[0069] (2) Cutting performance test: The test equipment is a spike® wireless cutting force test system produced by German pro-micro. The tool is a Φ10 mm 62-degree carbide end mill. The cutting fluid is mineral oil. The speed is 5000 rpm. The milling method is side milling. The tool feed speed is 800 mm / min. The cutting depth is 4 mm and the side cutting depth is 0.4 mm. Each sample is tested 3 times, and the average value is selected as the final result.

[0070] The performance test results of the embodiments and comparative examples are shown in Table 1. The hardness value 1 in Table 1 represents the hardness value of the first test. The hardness value 2 in Table 1 represents the hardness value of the second test. The hardness value 3 in Table 1 represents the hardness value of the third test. The hardness value 4 in Table 1 represents the hardness value of the fourth test. The bending moment 1 in Table 1 represents the bending moment value of the first test. The bending moment 2 in Table 1 represents the bending moment value of the second test. The bending moment 3 in Table 1 represents the bending moment value of the third test.

[0071] Table 1 Performance test results of embodiments and comparative examples

[0072] The metallographic photographs of each embodiment and comparative example after grinding and polishing are as follows: Figure 2-Figure 4 As shown, compared with the comparative example, the titanium alloy material in the embodiment introduces an easy-to-cut phase that is beneficial to cutting after alloying, thereby improving the cutting performance of the titanium alloy material.

[0073] It can be seen from Examples 1-2 that the higher the sulfur content, the lower the cutting bending moment of the alloy and the better the cutting performance; the higher the oxygen content in the alloy, the higher the hardness of the alloy, but the cutting bending moment will also increase and the cutting performance will decrease; although the hardness of the comparative example is low, sulfur is not added to improve the cutting performance, and the cutting performance is poor.

[0074] The above are exemplary embodiments disclosed in the present invention, but it should be noted that various changes and modifications may be made without departing from the scope of the embodiments disclosed in the claims. Although the elements disclosed in the embodiments of the present invention may be described or required in individual form, they may also be understood as multiple unless explicitly limited to the singular.

[0075] A person skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the disclosure of the embodiments of the present invention (including the claims) is limited to these examples; under the concept of the embodiments of the present invention, the technical features in the above embodiments or different embodiments can also be combined, and there are many other changes in different aspects of the above embodiments of the present invention, which are not provided in detail for the sake of simplicity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present invention should be included in the protection scope of the embodiments of the present invention.

Claims

1. A sulfur-containing free-cutting titanium alloy material without adding heavy metals, characterized in that: The composition of the sulfur-containing free-cutting titanium alloy material is calculated by mass percentage: S: 0.2~0.4%; O: 0.3~0.45%; B: 0.003~0.006%; C≤0.03%; N≤0.03%, the balance is titanium and unavoidable impurities.

2. The sulfur-containing free-cutting titanium alloy material according to claim 1, characterized in that: The composition of the sulfur-containing free-cutting titanium alloy material is calculated by mass percentage: S: 0.4%; O: 0.3%; B: 0.003%; C≤0.03%; N≤0.03%, the balance is titanium and unavoidable impurities.

3. The sulfur-containing free-cutting titanium alloy material according to claim 1, characterized in that: The composition of the sulfur-containing free-cutting titanium alloy material is calculated by mass percentage: S: 0.2%; O: 0.4%; B: 0.006%; C≤0.03%; N≤0.03%, the balance is titanium and unavoidable impurities.

4. A method for preparing raw material sponge titanium of sulfur-containing free-cutting titanium alloy material according to claim 1, characterized in that: The following steps are involved: S101. In the Kroll process, TiCl4 gas, H2S gas and BCl3 gas are simultaneously introduced into the reactor; S102. Titanium sponge particles having a maximum particle diameter of ≤6 mm are obtained by distillation and multi-stage crushing; S103. Spread the titanium sponge particles flat and place them in an oven at 500-550° C. for 50-90 minutes.

5. The method according to claim 4, characterized in that The multi-stage crushing includes three stages of crushing steps, namely jaw crushing, cone crushing and roller crushing, which are performed in sequence.

6. The method according to claim 4, characterized in that In step S101 , the molar ratio of Ti:S is controlled to be 99:(0.36-0.71), and the molar ratio of Ti:B is controlled to be 99:(0.006-0.012).

7. A method for preparing a free-cutting titanium alloy material from the titanium sponge particles obtained by the preparation method according to any one of claims 4 to 6, characterized in that: include: The titanium sponge particles are pressed into blanks; the blanks are stacked and placed in a TA1 package and vacuum-sealed; hot isostatic pressing and sintering are performed under argon protection to obtain square billets for rolling; the sintered square billets are heated to 900-930° C. and then rolled into free-cutting titanium alloy material discs through a hot rolling unit.

8. The method according to claim 7, characterized in that The step of "pressing titanium sponge particles into a blank" comprises: The titanium sponge particles are pressed into blanks at a pressure of 500 to 900 MPa.

9. The method according to claim 7, characterized in that: During the hot isostatic pressing step: The sintering temperature is 900-1000°C, the pressure is 90-100MPa, and the sintering time is 3-5h.

10. The method according to claim 9, characterized in that The heating rate of the hot isostatic pressing sintering is 2-5°C / min.

Citation Information

Patent Citations

  • Titanium slab for hot rolling, and production method therefor

    CN107075689A

  • Composite free-cutting steel containing sulfur, tin and titanium and vacuum induction preparation method thereof

    CN116121627A

  • Free-cutting titanium material and preparation process thereof

    CN118726793A

  • Modified titanium alloy capable of improving cutting performance, profile and preparation method of modified titanium alloy

    CN118880110A

  • Free-cutting ti alloy

    JP2003193159A

Cited By

  • Sulfur-fixing multi-element composite free-cutting titanium alloy and preparation method thereof

    CN120905561A